Fishing (in) the past to inform the future: Lessons from the histories of fisheries management in Lake Malawi and Mbenji Island - Wilson, David; Chirwa, Elias; Nkhoma, Bryson; Gough, Milo; Knapp, Charles W.; Morse, Tracy; Mulwafu, Wapulumuka (Marine policy, 2025)
Without historical interrogation of past and present fisheries management, governors and their sponsors often fall into the trap of replicating and reproducing failed approaches. Even when aimed at community empowerment, a lack of historical awareness can lead to underappreciation of the institutional, economic, and socio-ecological contexts that resource users navigate. In this article, we explore the history of fisheries management in Lake Malawi through comparative investigation of two enduring management regimes that developed in the mid-twentieth century: centralised fisheries management and the chief-led regime at Mbenji Island. We argue that the long-term successes of Mbenji Island fisheries in comparison to under-resourced and patchy governmental management has resulted from targeted technical regulations combined with robust leadership, proactive enforcement, sustained ecological and economic benefits, transparent processes, and embeddedness in existing institutions and beliefs. Yet, this regime has not existed in isolation from centralised management but, instead, has been directly and indirectly impacted by it. Pairing comparative historical analysis with analysis of fish specimens and water quality, we consider the underlying principles, long-term outcomes, and entanglements of these two regimes. Such an approach offers important insights into questions of governance legitimacy, the feedback between management regimes, and the role of science within management. Ultimately, the findings reported in this paper agree with recent surveys emphasising the need to focus on processes centred on participation and capacity building rather than set ecological outcomes within small-scale fisheries management. However, we argue that this requires deep historical awareness and reflection that is too often neglected. •The sustainability of fisheries at Mbenji Island is a result of integrated socio-political and resource-related principles.•Without historical awareness, reproduction of one-size-fits-all approaches to fisheries management remains all too common.•Fluidities between management contexts necessitates peer-to-peer engagement across leadership and institutional structures.•Management regimes must be analysed in a comparative context rather than in isolation or through a polarising lens.•Local decision-makers need to be leading participants in the determining research and decision-making agendas and processes.